Bridging innovation and sustainability: A systematic review of innovative work behavior and green practices - Mukapit, Mukhiffun; Daud, Siti Rohana; Selamat, Mohd Nasir (AMH International, 2024)
This systematic review explores the convergence of innovative work behavior (IWB) and green practices within organizations, aiming to bridge the critical gap between innovation and sustainability. The study synthesizes insights from academic literature to understand how IWB facilitates the adoption and enhancement of green practices and how these practices, in turn, support organizational sustainability. The review investigates the factors influencing employees’ green innovative work behavior (GIWB), identifying key drivers, mediators, and moderators that shape the relationship between environmental corporate social responsibility (ECSR) and GIWB. The findings provide theoretical and practical insights for encouraging sustainability through innovation in the workplace, emphasizing the roles of leadership, organizational culture, and employee engagement. Furthermore, the review highlights challenges and facilitators in incorporating IWB with green practices, featuring successful case studies and best practices across various industries. The study underscores the importance of creating a positive environment for innovation to achieve sustainable outcomes, offering valuable insights for policymakers, managers, and scholars dedicated to advancing the sustainability agenda through innovative approaches. The review concludes with recommendations for future research and practical implications for enhancing the synergy between innovation and sustainability in organizational contexts.